2016
DOI: 10.1177/0271678x16661567
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site laser Doppler flowmetry for assessing collateral flow in experimental ischemic stroke: Validation of outcome prediction with acute MRI

Abstract: High variability in infarct size is common in experimental stroke models and affects statistical power and validity of neuroprotection trials. The aim of this study was to explore cerebral collateral flow as a stratification factor for the prediction of ischemic outcome. Transient intraluminal occlusion of the middle cerebral artery was induced for 90 min in 18 Wistar rats. Cerebral collateral flow was assessed intra-procedurally using multi-site laser Doppler flowmetry monitoring in both the lateral middle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…a total of 210 operated rats to include 126 animals in the analysis. Of note, this is assuming that all the included animals have had an ischemia, which may be more difficult to ascertain without per-occlusion MRI (the conventional use of Laser Doppler Flowmetry having its own limitations) 51 . The additional advantage of using an MRI measurement of IS is that the brain may then potentially be used for evaluating mechanistic hypothesis rather than lesion size only, thus further refining the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…a total of 210 operated rats to include 126 animals in the analysis. Of note, this is assuming that all the included animals have had an ischemia, which may be more difficult to ascertain without per-occlusion MRI (the conventional use of Laser Doppler Flowmetry having its own limitations) 51 . The additional advantage of using an MRI measurement of IS is that the brain may then potentially be used for evaluating mechanistic hypothesis rather than lesion size only, thus further refining the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 This method of measuring changes in collateral flow was validated using MRI and perfusion-diffusion mismatch to visualize the penumbra. 26 We confirmed that distinct hemodynamic territories were being measured by the 2 probes during filament occlusion (Figure 1), making us confident that the change in flow measured by probe 2 was indeed collateral flow between the ACA and MCA territories. Using this approach, we found that collateral flow in vehicle-treated SHR was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…We used a validated method to measure changes in collateral flow by placing dual laser Doppler probes at two different sites over the core and peri-infarct vascular territories. 25,26 This method of measuring changes in collateral flow was validated using MRI and perfusion-diffusion mismatch to visualize the penumbra. 26 We confirmed that distinct hemodynamic territories were being measured by the 2 probes during filament occlusion (Figure 1), making us confident that the change in flow measured by probe 2 was indeed collateral flow between the ACA and MCA territories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A paramedian skin incision was performed, and the subcutaneous tissue and cranial fascia were dissected to reach the skull bone. The probe of the monitor was placed at the settled skull bone area to detect the CBF (Cuccione et al, 2016). CBF changes in the rats were monitored before 2VO operation at the following successive periods: 1, 6, 24 h, 3, 7, 14, and 28 days after operation, as well as 1, 7, 14, and 28 days after drug treatment.…”
Section: Methodsmentioning
confidence: 99%